Anti-virulence properties of catechin-in-cyclodextrin-in-phospholipid liposome through down-regulation of gene expression in MRSA strains. (June 2022) - Sinsinwar, Simran; Jayaraman, Adithyan; Mahapatra, Santanu Kar; Vellingiri, Vadivel
Abstract: Methicillin resistant Staphylococcus aureus (MRSA) is a prime pathogen responsible for various infections in human beings. Expression of virulence factors is a biggest challenge in MRSA, which results in failure of conventional antibiotic therapy. In connection to the search for natural and safe anti-virulence compounds, the present study focused to evaluate the anti-virulence potential of catechin-in-cyclodextrin-in-phospholipid liposome (CCPL) on MRSA strains. CCPL inhibited young biofilm (64.15–72.70%) as well degraded mature biofilm (55.60–63.65%) at ½ and ¼ MIC doses, which was further confirmed by scanning electron microscopy and confocal laser scanning microscope studies. CCPL was capable enough to modify the surface hydrophobicity (40.26–48.59%), reduce the EPS production (1.71–2.25 folds) and bacterial motility. In addition, CCPL inhibited the synthesis of virulence factors like slime production (0.40–0.50 folds), DNase production, hemolytic activity (28.08–49.07%), proteolytic production (14.65–18.04%), lipase production, autolysis and cell auto-aggregation. CCPL prevented the staphyloxanthin production and thereby increased the susceptibility of MRSA strains towards H2 O2 . Further, CCPL significantly down-regulated the virulence genes ( agrA, agrC, clfA, clfB, fnbA, fnbB, icaA, icaD, hla, hld, rna III, atlA, sarA, sigB & geh ). Thus, the results of present study revealed that the CCPL can effectively reduce the virulence properties and its application could inhibit the pathogenicity and also prevents the development of drug-resistance in MRSA strains. Highlights: Anti-virulence potential of catechin-in-cyclodextrin-in-phospholipid liposome (CCPL) was investigated in MRSA strains. CCPL inhibited young biofilm, mature biofilm, modified the surface hydrophobicity, reduced the EPS production and bacterial motility. CCPL inhibited the synthesis of slime production, DNase production, hemolytic activity, proteolytic production, lipase production, autolysis and cell auto-aggregation. CCPL prevented the staphyloxanthin production and thereby increased the susceptibility of MRSA strains towards H2 O2 . CCPL significantly down-regulated the virulence genes and hence its application could inhibit the pathogenicity and prevents the development of drug-resistance in MRSA strains.